PERBAIKAN PRODUKSI TANAMAN JAGUNG PADA ULTISOL MENGGUNAKAN ABU TERBANG BATUBARA DAN KOMPOS TANDAN KOSONG KELAPA SAWIT - Retno Wilujeng; Eko Handayanto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
The potential of Ultisols, especially in East Kalimantan for the development of food crop agriculture is faced with constraints on phosphorus availability due to low soil pH and high solubility of aluminum (Al). The purpose of this study was to elucidate the effect of a combination application of coal fly ash (CFA) and oil palm empty fruit bunches (OPEFB) on the availability of phosphorus in an Ultisol from East Kalimantan and its impact on the production of maize. The combination of CFA and OPEFB consisted of seven treatments with three replications. The research was carried out in two steps. The first experiment (incubation in the laboratory), was carried out under non-leaching condition for 42 days. Parameters observed included soil pH, available soil P, total soil P, and soil exchangeable Al. The second experiment (growth experiments in a glasshouse), was were carried out by growing maize plants with the same treatment as for experiment 1. The plant height and leaf area were observed every week. At the harvest time (age 12 weeks), dry weight of shoots and roots, maize weight with cobs, and maize weight without cobs were observed. The results of soil incubation showed the decrease in the soil exchangeable Al- level, the increase in soil total-P, and soil available-P. The combination application of CFA and OPEFB did not have a significant impact on soil pH, and soil organic-C. The results of the glasshouse experiment showed that CFA and OPEFB were not significantly different in the parameters of plant height, leaf area of 12 weeks, weight of shoots and roots, maize weight with cobs, and maize weight without cobs.